Alternative politics the German Green Party - Poguntke, Thomas 1959- (Edinburgh Univ. Press, 1993)
The political success of the German Green Party during the 1980s spearheaded the 'green wave' in other West European democracies. Indeed, despite their defeat in 1990, the Greens still hold the balance of power in several Land parliaments and stand a good chance of making a comeback in the 1994 Bundestag elections. This book is the first comprehensive account of the organisation ideology and political style of the German Greens. Comparing them to established parties, the book gives a full account of the German party system, and assesses the adaptability of both types of party to a changing social and political environment in the new Europe. It examines intra-party political culture, the social profiles of voters and party activists, and the party's place in the context of the 'New Politics'. A challenging read suitable for advanced undergraduates and graduates studying the West European political system.
Keywords: Grünen (Political party) -- History; Die Grünen; Geschichte 1900-2000; Grünen; Geschichte; Politik; Deutschland; Germany -- Politics and government -- 20th century